THE PSYCHOLOGICAL IMPACT ON PERIOPERATIVE HEALTHCARE WORKERS DURING COVID-19: A PROSPECTIVE LONGITUDINAL THEMATIC ANALYSIS - Atallah Theyab Khalaf Albathali, Awayed Ramadan awad Albathali, Fawaz Misheal Eawad Almutairi, Mohammed Nawban Hammed Almutairi, Senaid Mohammed Senaid Aljameeli, Nader Mohammad Jassi Aldaihani, (Chelonian Research Foundation, 2022)
Healthcare workers have faced immense pressures during the COVID-19 pandemic that have profoundly impacted mental health, yet limited research has adopted in-depth longitudinal approaches to capture lived experiences. This expansive prospective longitudinal qualitative study examined escalating psychological effects on 130 perioperative physicians, nurses and technicians across 5 hospitals in KSA during a severe second COVID-19 wave. Participants completed up to 5 sets of monthly semi-structured video interviews exploring experiences in depth. Rigorous thematic analysis of the extensive interview data revealed alarming impacts including pervasive anxiety around viral transmission, grief and trauma from constant patient deaths, physical and emotional exhaustion, and moral injury from resource limitations forcing impossible care rationing. However, clinicians exhibited resilience through camaraderie, optimistic mindsets, cognitive reframing, leisure pursuits, exercise, boundary setting, and support systems. Detailed recommendations encompass improving staffing, mental health resources, workplace flexibility and leave policies, peer support programs, team building, mentoring, counseling, leadership rounding, and mindfulness initiatives to protect caregiver wellbeing when recurrent pandemic waves require delivering unrelenting, self-sacrificial care. This expansive study provides unparalleled insights into the mental health effects of prolonged pandemic pressures on frontline healthcare workers revealing concerning trajectories but also sources of resilience during perpetual crisis. The findings have implications for organizations globally in developing multifaceted evidence-based strategies to support clinician wellbeing during future infectious disease outbreaks or other disasters requiring surging, sustained care delivery. Keywords: COVID-19, mental health, perioperative, thematic analysis, longitudinal, qualitative